PENGARUH PEMASARAN HUBUNGAN TERHADAP LOYALITAS NASABAH - Yelnovatri Patandianan; Patwayati Patwayati; Nasrul Nasrul (Pascasarjana Universitas Halu Oleo, 2019)
The purpose of this study was to find out: (1) satisfaction partially affects loyalty. (2) trust partially influences loyalty. (3) commitment partially affects loyalty. (4) satisfaction, trust and commitment simultaneously influence customer loyalty Simpeda Bank Sultra Savings Kolaka Branch. This research is a survey research. The population in this study were customers using the Simpeda Bank Sultra Cabang Kolaka, based on 9108 respondents. The total sample in this study amounted to 100 respondents. The sampling technique uses accidental sampling. Methods of data collection using questionnaires and data analysis using multiple linear regression analysis with the help of SPSS Version 16.0. The results of this study indicate: (1) satisfaction partially has a significant effect on loyalty. (2) trust partially has a significant effect on loyalty. (3) commitment partially has a significant effect on loyalty. (4) satisfaction, trust, and commitment simultaneously have a significant effect on customer loyalty Simpeda Bank Sultra Cabang Kolaka. Keywords: satisfaction, trust, commitment, and loyalty